Intranasal insulin in Alzheimer disease (diabetes in situ?): a systematic review and meta-analysis - Luís Jesuíno de Oliveira Andrade; Gabriela Matos; Luís Matos de Oliveira (Dementia & Neuropsychologia)
ABSTRACT. Alzheimer disease (AD) is a neurodegenerative disorder. Evidence suggests that AD shares pathophysiological similarities with type 2 diabetes. Intranasal insulin (INI) has emerged as a potential therapeutic approach for AD by directly targeting the brain and modulating insulin signaling pathways. Objective: To evaluate the efficacy and safety of INI therapy for AD through a systematic review and meta-analysis of randomized controlled trials. Methods: A search of electronic databases, including PubMed, Web of Science, Scopus, and Embase, was conducted to identify relevant studies published up to June 2024. Inclusion criteria encompassed peer-reviewed original research articles focused on humans, investigating the therapeutic effects of INI administration on cognitive impairment associated with AD, and reporting quantitative data on cognitive outcomes, biomarkers, or pathological markers relevant to AD. A meta-analysis was conducted to quantitatively synthesize the effects of INI on cognitive outcomes. Results: A total of 647 articles were identified, and eight studies met the inclusion criteria. The overall odds ratio was 3.75 (95%CI 1.49–9.40). The test for overall effect showed a statistically significant difference (p<0.05). However, the I2 value indicated a high level of heterogeneity (85.5%), suggesting significant variability among the studies. Conclusion: While the current data is not yet conclusive enough to definitively establish INI as a standard treatment for AD, the evidence supporting its safety, efficacy, and reduced risk of systemic side effects suggests potential cognitive benefits for improving global cognition in patients with AD.